Gold nanoparticles make chitosan–streptomycin conjugates effective towards Gram-negative bacterial biofilm. Issue 11 (21st January 2016) - Mu, Haibo; Liu, Qianjin; Niu, Hong; Sun, Yuelin; Duan, Jinyou
Abstract : The emergence of biofilm-associated resistance of microbes to traditional antibiotics has resulted in an urgent need for novel antimicrobial agents. Abstract : The emergence of biofilm-associated resistance of microbes to traditional antibiotics has resulted in an urgent need for novel antimicrobial agents. Herein we developed a facile approach to overcome the problem through chitosan–streptomycin gold nanoparticles (CA NPs). The synthesized CA NPs were characterized by ultraviolet-visible absorption spectra (UV-vis), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS). The resulting CA NPs maintained their antibiofilm activities towards Gram-positive organisms. More importantly, CA NPs damaged established biofilms and inhibited biofilm formation of Gram-negative bacteria pathogens. Mechanistic insight demonstrated that CA NPs rendered streptomycin more accessible to biofilms, thereby it was available to interact with biofilm bacteria. Additionally, CA NPs were observed to kill more biofilm-dispersed cells than CS conjugate or streptomycin and inhibit the planktonic cell growth of Gram-positive and -negative bacteria. Thus, this work represents an innovative strategy whereby gold nanoparticles linked to carbohydrate–antibiotic conjugates can overcome antibiotic resistance of microbial biofilms, suggesting the potential of using the generated CA NPs as antimicrobial agents for bacterial infectious diseases.